(Re) contando a história da Previdência Social no Brasil e em Mato Grosso na voz dos seus/as sujeitos/as - Soares, Aparecida de Castro (2011)
With the worsening of the social issue and the needs imposed by the current model of production, the access to the public policies becomes, many times, the only way of addressing the social needs of individuals that form the working class and are not inserted in the labor market. In this context some social rights, while historical acquisition of the workers, are the targets of a strong dismantling promoted by the economic and political elite of Brazil. In this way, understanding and reflecting about the trajectory configurations of the implementation of a public policy is essential to design confrontation strategies to the ideals of dismantling to which the same is submitted gradually. The Social Welfare system, as a public policy, aims at assisting the workers and their families in moments that are considered non-appropriate for the insertion in the labor market, due to diseases, accidents, pregnancy, imprisonment, old age or death. In this sense, the study aims mainly at the theme of Public Policy, in particular, the Social Welfare Policy in which the General System of Social Welfare stands out. The research used the quantitative and qualitative analysis, focusing mainly on the latter. In its development complementary readings and surveys about knowledge production on the theme chosen were done stimulating new debates. The literature review occurred through books, dissertations, theses and material available in the internet. In the data collection primary and secondary sources were used. Some results of the research affirm that currently there are many configurations that permeate the trajectory of the social welfare policy, where the conceptual conceptions of categories in the daily routine of the policy, in which the inefficiency of the public policy is emphasized with the aim of strengthening the social security offered through the market, materialized by the financial institutions. With rare exceptions, there is no perception of the users that are seeking for a right recognized constitutionally and that must be understood as such. In this study, it is concluded that even though the State acts in a mix of different positions it will depend on the power established upon it. However, it is observed that there are advances in the conceptions of the themes highlighted in the research, even though the subjects that are interviewed come from different political areas, that is, professionals that worked in agencies, heads of sections and managing positions. In this sense, it is of fundamental importance that one must have as a direction the defense of a public and qualified social welfare policy, be it through the benefits and services legally established, be it in the professional performance of this policy. It is considered that this perception can contribute to broaden the access of the population to the social rights and act in the consolidation of these rights in the perspective of justice.